THYROID AUTOIMMUNE DISEASE AND EFFECT ON DEVELOPMENT TO THYROID CANCER - Tuamah, Mustafa Raheem (Antis-Publisher, 2025)
Objective: This study investigates the association between autoimmune thyroid diseases—specifically Hashimoto's thyroiditis (HT) and Graves' disease (GD)—and the development of thyroid cancer, with a primary focus on papillary thyroid carcinoma (PTC). Method: A comprehensive literature review was conducted to analyze epidemiological trends, immunopathological mechanisms, and tumor microenvironment factors linking autoimmunity to thyroid carcinogenesis. Results: The findings indicate a significant correlation between autoimmune thyroid disorders and increased incidence of PTC, suggesting that chronic inflammation may contribute to oncogenic genetic alterations in thyroid epithelial cells. Interestingly, HT appears to paradoxically confer favorable clinical outcomes, including reduced tumor aggressiveness, enhanced responsiveness to radioiodine therapy, and improved survival, likely due to heightened immune surveillance. Additionally, the presence of cancer-associated fibroblasts (CAFs) was associated with increased lymph node metastasis, highlighting their role in shaping a pro-tumorigenic microenvironment. Novelty: This study provides integrative insights into the dual role of autoimmunity in both promoting and modulating thyroid cancer progression, and underscores the importance of the tumor microenvironment—particularly CAFs—in influencing metastatic behavior in PTC.